Retracted: A Chronicle Overview of Cephalometric Parameters for assessing Sagittal Jaw Disparity - Dubey, Jaina; Kallury, Amitabh; Balani, Rajesh Kumar; Bharti, Chandni; Dubey, Chandrika (Orthodontic Journal of Nepal, 2021)
“A Chronicle Overview of Cephalometric Parameters for assessing Sagittal Jaw Disparity.” was retracted. See Retraction Notice DOI: https://doi.org/10.3126/ojn.v15i2.94942